The Effect Of Giving Kangaroo Mother Care Method On The Stability Of Body Temperature In Low Birth Weight (LBW) Infants : A Literature Review - Winda Afikirtiani (Journal of Applied Health Management and Technology, 2022)
ABSTRAKBackground : Low Birth Weight Babies are newborns who weigh less than 2500 grams at birth. The LBW mortality rate is 35x higher than for babies with birth weights of more than 2500 grams. The method used in caring for babies with low birth weight is Kangaroo Mother Care (KMC). KMC is an effective way to meet baby's basic needs, namely warmth, breast milk, and affection. Purpose : Analyze the effectiveness of the KMC method for body temperature stability in low birth weight infants. Methods : Determine the topic, determine the formulation of the problem, determine the objectives, search for data sources and journal selection. Journal search uses electronic databases namely google scholar, Wiley, and Pub Med, with the keywords used “metode kangaroo mother care, kestabilan suhu tubuh, BBLR or kangaroo mother care method, stability of body temperature, LBW”. Results : The journals that were sampled in this study were 14 journals resulting from experimental research and literature studies with the results of the Kangaroo Mother Care Method affecting the stability of body temperature in low birth weight babies (LBW). Conclution : From the literature study it can be concluded that there is an effect of giving kangaroo mother care method to the stability of body temperature in low birth weight babies with p value 0.05.